Fenomenologia feminista: uma análise crítica - Dornelles, Tatiana Almeida de Andrade (2024)
The present work arises from the questioning of what, after all, it means to be a woman. In the last decade, there has been an exponential growth of a political-ideological movement that advocates the conception of woman as a product of discourse, an idea, or the result of a performance. Phenomenology, with its classical theoretical foundation, promises a different approach: the encounter with the things themselves. Under the light of concepts from the phenomenological tradition such as embodied consciousness, facticity, and lifeworld, the phenomenological promise would be responsible for the desired reconciliation between the data of reality and a philosophical approach that protects the female human being from being erased as a political group. Phenomenology revolutionizes philosophy by asserting the body as an indispensable category for thinking about the subject. Thus, after the presentation of the preliminary discussion, this work exposes what phenomenology is, through the ideas of its founder, Edmund Husserl, and Merleau-Ponty, one of the main proponents of the school who dedicated himself especially to the study of corporeality. Simone de Beauvoir, in turn, demonstrates that this body, this subject, is always of a certain sex, ushering in the era of feminist phenomenology. But is the mentioned promise being fulfilled? This dissertation, therefore, aims to conduct an exhaustive literature review of Brazilian academic production on the theme of feminist phenomenology. Subsequently, it navigates through foreign literature, especially the most iconic texts on the subject and the published books that have received the most attention. Finally, the fourth chapter, based on the literature review, aims to discuss and analyze the state of the art of feminist phenomenology, demonstrating the change in focus of interest over the years.